Never knowing - Stevens, Chevy (St. Martin's Press, 2011)
Struggling with a need for closure, Sara Gallagher attempts to reconnect with her birth parents only to learn that her biological father is an infamous serial killer, a discovery that causes her to fear she has inherited violent tendencies.